Economic Satisfaction of Street Vendors after Teras Samarinda Development: A Qualitative Study in Samarinda City - Karlina Wati; Sutrisno; Reza; Vitria Puri Rahayu (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the economic satisfaction of street vendors after the development of Teras Samarinda in Samarinda City based on indicators of sales volume, business profit, and financial goal attainment. This study employed a descriptive qualitative approach using primary data obtained through in-depth interviews with five street vendors who were selected purposively based on their experience of operating businesses both before and after the development of Teras Samarinda. Data were analyzed through data reduction, data display, and conclusion drawing techniques. To enhance data credibility, time triangulation was applied through data collection conducted at different times and days. The findings indicate that economic satisfaction has not been optimally achieved among the interviewed vendors, as reflected in declining sales volume, reduced customer numbers, and unstable daily income compared to conditions before the development. Most vendors' profits were only sufficient to cover operational expenses, causing financial goals such as savings, capital growth, and business expansion to remain largely unmet. The study concludes that economic satisfaction tended to be low among the interviewed vendors, although they continue maintaining their businesses as an adaptation strategy to survive in a changing business environment